INNOVATIVE ENVIRONMENTAL PACKAGING FOR SEPARATING STORAGE OF TWO COMPONENTS, ALLOWING TO EXTEND THE LIFETIME WITHOUT PRESERVATIVES - ESHBAEVA, ULBOSIN; Vladimir, Litvyak; Ergashev, Mamurjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
A container for separate storage of two components was developed, which allows to increase the functionality and reliability of containers, increase the volume of the container for the additional component and its shelf life, prepare working mixtures immediately before their use, simplify the design, using the standard capacity as a container for one of the components, facilitate assembly containers and its operation. Container elements (container for the main component, core for rupture of the membrane, container for the additional component, protective glass, lid, gasket and membrane) are made using easily recyclable and biodegradable materials.